The long-term surgical outcomes of the Aurolab aqueous drainage implant versus the Ahmed glaucoma valve for refractory pediatric glaucoma in Saudi children - Abdullah M Khan; Khabir Ahmad; Motazz Alarfaj; Humoud Alotaibi; Rizwan Malik; Konrad Schargel (Indian Journal of Ophthalmology)
Introduction: Glaucoma drainage devices (GDDs) play a crucial role in managing refractory pediatric glaucoma. The Aurolab aqueous drainage implant (AADI) is a promising option, especially in regions where cost-effective interventions are essential. We aimed to assess the long-term outcomes of AADI compared to the Ahmed glaucoma valve (AGV) in Saudi children. Methods: A cohort study was conducted at a tertiary eye care center in Riyadh, including patients ≤18 years who underwent AADI or AGV implantation between July 2014 and November 2019. Primary outcomes were intraocular pressure (IOP) control, anti-glaucoma medication (AGM) usage, the need for additional glaucoma surgery, and complications. Factors associated with treatment failure were examined using Cox proportion hazard modeling. Results: Among 126 eyes (AADI = 56, AGV = 70), the mean follow-up was 55.52 ± 14.47 and 53.02 ± 21.85 months for AADI and AGV, respectively. AADI demonstrated comparable IOP control and AGM reduction to AGV over five years. The AADI group exhibited higher success rates than AGV (76.8% vs. 47%). AGV showed a significantly higher risk of failure compared to AADI (adjusted hazard ratio 2.75, P = 0.041). Conclusion: AADI proves to be a safe and effective option for refractory pediatric glaucoma. The long-term outcomes of AADI were not inferior to AGV. Despite consistently lower IOP and AGM usage in the AADI group from the 3rd to the 60th month, statistical significance was not achieved.